CEACAM Gene Family Mutations Associated With Inherited Breast Cancer Risk – A Comparative Oncology Approach to Discovery - Huskey, Anna L. W.; McNeely, Isaac; Merner, Nancy D. (Frontiers in Genetics, 2021)
Introduction: Recent studies comparing canine mammary tumors (CMTs) and human breast cancers have revealed remarkable tumor similarities, identifying shared expression profiles and acquired mutations. CMTs can also provide a model of inherited breast cancer susceptibility in humans; thus, we investigated breed-specific whole genome sequencing (WGS) data in search for novel CMT risk factors that could subsequently explain inherited breast cancer risk. Methods: WGS was carried out on five CMT-affected Gold Retrievers. Protein truncating variants (PTVs) within human orthologs detected in all five samples were validated and genotyped in the 13 remaining CMT-affected Golden Retrievers. Allele frequencies were compared to canine controls. Subsequently, human blood-derived exomes from The Cancer Genome Atlas breast cancer cases were analyzed and allele frequencies were compared to Exome Variant Server ethnic-matched controls. Results: Carcinoembryonic Antigen-related Cell Adhesion Molecule 24 (CEACAM24) c.247dupG;p.(Val83Glyfs*48) was the only validated variant and had a frequency of 66.7% amongst the 18 Golden Retrievers with CMT. This was significant compared to the European Variation Archive (p-value 1.52x10-8) and non-Golden Retriever American Kennel Club breeds (p-value 2.48x10-5). With no direct ortholog of CEACAM24 in humans but high homology to all CEACAM gene family proteins, all human CEACAM genes were investigated for PTVs. A total of six and sixteen rare PTVs were identified in African and European American breast cancer cases, respectively. Single variant assessment revealed five PTVs associated with breast cancer risk. Gene-based aggregation analyses revealed that rare PTVs in CEACAM6, CEACAM7, and CEACAM8 are associated with European American breast cancer risk, and rare PTVs in CEACAM7 are associated with breast cancer risk in African Americans. Ultimately, rare PTVs in the entire CEACAM gene family are associated with breast cancer risk in both European and African Americans with respective p-values of 1.75x10-13 and 1.87x10-04. Conclusion: This study reports the first association of inherited CEACAM mutations and breast cancer risk, and potentially implicates the whole gene family in genetic risk. Precisely how these mutations contribute to breast cancer needs to be determined; especially considering our current knowledge on the role that the CEACAM gene family plays in tumor development, progression, and metastasis.